ANALISIS KOMPETENSI DAN KETERSEDIAAN TENAGA KEPENDIDIKAN SEKOLAH DASAR DI INDONESIA - Ananda, Rizki; Khairani, Masita; Amalia Putri, Nur Annisa; Anggraini, Tiara; Pratiwi, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education personnel play a crucial role in the success of primary education, yet they continue to face challenges related to competence, distribution, and professional development. This study aims to examine the conditions of competence and availability of education personnel in Indonesian primary schools, as well as to analyze the issues related to their quality. Education personnel, consisting of both teaching and non-teaching staff, play a vital role in supporting the learning process and school operations. However, the unequal distribution of educators, the shortage of adequately competent personnel, and the limited opportunities for training and professional development remain major challenges. This research employs the Systematic Literature Review (SLR) method to analyze various relevant previous studies. The findings indicate that the competence of educational personnel particularly in pedagogical, professional, social, and personal aspects still needs improvement. Equitable availability of education personnel, effective training, and fair placement policies are also critical factors in enhancing education quality. Therefore, systematic efforts and inclusive policies are required to address these issues and achieve better quality in primary education in Indonesia.